Parametric robust optimization of the digital flight control systems - Tunik, A. A.; Abramovich, E. A. (Proceedings of National Aviation University (archive), 2003)
The paper is devoted to the parametric optimization of the digital flight control systems from the viewpoint of achieving the necessary compromise between their robustness and performance. This compromise could be reached by using modern approach of multi-model H2 /Н robust optimization, which was described mainly for continuous systems. In this paper the optimization procedure for discrete control systems is proposed. Its efficiency is illustrated by the example of the digital flight control of the small Unmanned Aerial Vehicle